Realisasi Active Learning pada Pembelajaran Bahasa Inggris dalam Konteks Pendidikan Keperawatan - Deddy Suryana; Amanda Puspanditaning Sejati; Agus Suherman (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
Distance learning is a challenge in the implementation of health education. The Government of Indonesia recommends the Merdeka Belajar – Kampus Merdeka policy which carries the concept of active learning to be implemented at the college level, including health education. In connection with this, the studies of active learning models in the context of medical education during the COVID-19 period has not been widely reviewed. Therefore, this study aims to explore the implementation of active learning model in English for Professional Nurses subject in a nursing study program in one of the universities in Indonesia. This research employed descriptive research design with qualitative approach. The subject of this study was 1 lecturer. Data and its collection techniques were the learning activities data taken using observations and interviews. The results of this study showed that active learning model can be implemented in asynchronous learning. This research is expected to give overview of active learning in higher education context.